1963
DOI: 10.1530/acta.0.0440107
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Binding of Cortisol by Transcortin

Abstract: By means of a gel filtration on Sephadex columns the plasma corticoids can be separated into two fractions: namely a fraction bound to a macromolecular agent and an unbound fraction. When plasma is overloaded with cortisol before gel filtration, the binding capacity of the macromolecular agent can be evaluated. The bound corticoids can be measured quantitatively either fluorimetrically or colorimetrically. The macromolecular binding agent behaves like transcortin in a series of experiments. Various exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1965
1965
1979
1979

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…If we measure the percentage inhibition with respect to the binding capacity at pH 8.0, it can be seen that 93% of the binding power is lost at pH 4.0. This result is similar to the appearance of heat-inactivated trans- These binding affinities determined on pure human transcortin corroborate the results obtained on whole serum [7,14] but the polymerization at low pH has never been observed as impure human transcortin does not polymerise [4]. see four dichroic bands at 320,290,236 and 200 nm.…”
Section: Influence Of Ph On the Stability Of Pure Transcortinsupporting
confidence: 87%
See 2 more Smart Citations
“…If we measure the percentage inhibition with respect to the binding capacity at pH 8.0, it can be seen that 93% of the binding power is lost at pH 4.0. This result is similar to the appearance of heat-inactivated trans- These binding affinities determined on pure human transcortin corroborate the results obtained on whole serum [7,14] but the polymerization at low pH has never been observed as impure human transcortin does not polymerise [4]. see four dichroic bands at 320,290,236 and 200 nm.…”
Section: Influence Of Ph On the Stability Of Pure Transcortinsupporting
confidence: 87%
“…Inactivated transcortin was obtained by incubating a solution of 10 mg of transcortin/l ml of distillated water at 60°C for 30 min. Indeed, De Moor et al [7] have shown that human transcortin was irreversibly inactivated at this temperature.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The introduction of the adsorption step provides for complete removal of endogenous steroids from plasma without damaging transcortin. Other stripping procedures seem to be less or not at all suitable: Extraction with organic solvents leads to an irreversible denaturation of transcortin, whereas dialysis against bovine albumine at 40 °C fails to remove the endogenous steroids sufficiently (15). Gel filtration at 46 °C (16; own experiments) or at pH 5.0-5.5 (17) brings about the desired stripping effect, yet it lacks the technical simplicity of the adsorption technique.…”
Section: Discussionmentioning
confidence: 99%